A rare case of coronary artery fistula presented with acute myocardial infarction - Smettei, Osama Abdalhadi; Abazid, Rami Mahmood (Avicenna Journal of Medicine, 2015)
Coronary artery fistulas (CAFs): Are anomalous connections of the coronary arteries (CA) with major vascular structures or heart chambers. Most of CAFs are incidental findings during invasive coronary angiography (ICA) or computed tomography angiography (CTA). Many patients with CAFs are asymptomatic; only a minority has been associated with various clinical features and outcomes. We have reported a rare CAF complicated with acute myocardial infarction (AMI) in 43 years old female Patient who was admitted to our institution with a Diagnosis of Acute Infero-Posterior Myocardial Infarction (AMI). ICA and CTA showed a thrombosed CAF between left main coronary artery and right atrium with totally occluded left circumflex artery by a thrombus extended from the fistula. As there was a high risk associated with immediate intervention, the patient was kept on conservative management with a future plan of catheter-assisted or surgical closure. We have shown a rare case of CAF presenting with AMI that is unusual for such an anomaly, and have highlighted the role of CTA in the diagnosis and management of such rare disorder.
Keywords: Acute myocardial infarction; computed tomography angiography; coronary anomalies; coronary artery fistula